Twentieth-Century Southern Literature - Bryant, J. A., Jr (Book collections on Project MUSE., 2015)
Authors discussed include: Wendell Berry, Erskine Caldwell, Truman Capote, Ralph Ellison, William Faulkner, Shelby Foote, Zora Neal Hurston, Bobbie Ann Mason, Cormac McCarthy, Flannery O'Connor, William Styron, Anne Tyler, Alice Walker, Robert Penn Warren, Eudora Welty, Tennessee Williams, Thomas Wolfe, Richard Wright, and many more. By World War II, the Southern Renaissance had established itself as one of the most significant literary events of the century, and today much of the best American fiction is southern fiction. Though the flowering of realistic and local-color writing during the fir.